Proactive Personality and Social Support With Pre-retirement Anxiety: Mediating Role of Subjective Career Success - Ugwu, Lawrence Ejike; Enwereuzor, Ibeawuchi K.; Nwankwo, Barnabas E.; Ugwueze, Stella; Ogba, Franscisca N.; Nnadozie, Evelyn E.; Elom, Chinyere O.; Eze, Angela; Ezeh, Michael A. (Frontiers in Psychology, 2021)
The main objective of this paper is to investigate the mediating role of subjective career success in the relationship between proactive personality, social support and pre-retirement anxiety. Using a two-wave longitudinal design, 624 pre-retirees were sampled (M=56.49 years; SD = 4.56); of these, 237 (37.98%) were males and 387 (62.02%) females. Measurement Model and mediation test were performed using SmartPLS and IBM AMOS. Result indicated that proactive personality, social support and subjective career success showed negative relationships with the dimensions of pre-retirement anxiety (financial preparedness, social obligation and social alienation). Subjective career success mediated the relationship between proactive personality and pre-retirement anxiety.